2018
DOI: 10.1016/j.stemcr.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Oxidative Stress Impairs Hematopoietic Progenitor Function in C57BL/6 Substrains

Abstract: SummaryC57BL/6N (N) and C57BL/6J (J) mice possess key genetic differences, including a deletion in the Nicotinamide nucleotide transhydrogenase (Nnt) gene that results in a non-functional protein in J mice. NNT regulates mitochondrial oxidative stress. Although elevated oxidative stress can compromise hematopoietic stem and progenitor cell (HSPC) function, it is unknown whether N- and J-HSPCs are functionally equivalent. Here, we report that J-HSPCs display compromised short-term hematopoietic repopulating act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Given the data presented herein and elsewhere ( Bourdi et al, 2011 ; Fontaine and Davis, 2016 ; Leskov et al, 2017 ; McCambridge et al, 2019 ; Mekada et al, 2009 ; Rao et al, 2020 ; Ripoll et al, 2012 ; Rydström, 2006 ; Toye et al, 2005 ; Vozenilek et al, 2018 ) and given that redox regulation affects many cellular processes ( Gambhir et al, 2019 ; Lingappan, 2018 ; Sun et al, 2020 ), Nnt emerges as a legitimate focus of concern. In addition, the presence of Nnt exons 8–12 provides a useful genetic marker to illustrate that a mouse strain is not on a pure 6J background, with genetic backgrounds, as shown herein and elsewhere, able to have a profound influence on phenotype ( Leskov et al, 2017 ; Morales-Hernandez et al, 2018 ; Salerno et al, 2019 ; Vozenilek et al, 2018 ; Williams et al, 2021 ; Wolf et al, 2016 ). We thus undertook a k-mer mining approach to interrogate the NCBI SRA ( Figure 8—figure supplement 1a ), which (at the time of analysis) contained 61,443 RNA-Seq Run Accessions listing ‘C57BL/6J’ in the strain field of the metadata.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Given the data presented herein and elsewhere ( Bourdi et al, 2011 ; Fontaine and Davis, 2016 ; Leskov et al, 2017 ; McCambridge et al, 2019 ; Mekada et al, 2009 ; Rao et al, 2020 ; Ripoll et al, 2012 ; Rydström, 2006 ; Toye et al, 2005 ; Vozenilek et al, 2018 ) and given that redox regulation affects many cellular processes ( Gambhir et al, 2019 ; Lingappan, 2018 ; Sun et al, 2020 ), Nnt emerges as a legitimate focus of concern. In addition, the presence of Nnt exons 8–12 provides a useful genetic marker to illustrate that a mouse strain is not on a pure 6J background, with genetic backgrounds, as shown herein and elsewhere, able to have a profound influence on phenotype ( Leskov et al, 2017 ; Morales-Hernandez et al, 2018 ; Salerno et al, 2019 ; Vozenilek et al, 2018 ; Williams et al, 2021 ; Wolf et al, 2016 ). We thus undertook a k-mer mining approach to interrogate the NCBI SRA ( Figure 8—figure supplement 1a ), which (at the time of analysis) contained 61,443 RNA-Seq Run Accessions listing ‘C57BL/6J’ in the strain field of the metadata.…”
Section: Resultsmentioning
confidence: 81%
“…NNT thereby sustains mitochondrial antioxidant capacity through generation of NADPH ( Ward et al, 2020 ), with the loss of active NNT in 6J mice associated with reduced ability to detoxify reactive oxygen species (ROS) via the glutathione and thioredoxin pathways ( McCambridge et al, 2019 ; Meimaridou et al, 2018 ; Ronchi et al, 2013 ; Rydström, 2006 ). As redox regulation is involved in many cellular processes ( Gambhir et al, 2019 ; Lingappan, 2018 ; Sun et al, 2020 ) and genetic backgrounds are known to affect phenotypes ( Leskov et al, 2017 ; Morales-Hernandez et al, 2018 ; Rao et al, 2020 ; Salerno et al, 2019 ; Vozenilek et al, 2018 ; Williams et al, 2021 ; Wolf et al, 2016 ), we sought to determine how many other studies in GMO mice might have been affected by 6J vs. 6N background differences using the Nnt gene as a genetic marker. k-mer mining of RNA-Seq datasets deposited in the NCBI Sequence Read Archive (SRA) revealed that ≈27% of Run Accessions and ≈38% of BioProjects listing the mouse strain as ‘C57BL/6J’ had Nnt reads inconsistent with a 6J background.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we wondered how general our results are. On the one hand, even in the C57BL/6 strain we used, mice from substrains J and N display genetic and phenotypic differences, some of which are immune related 60 . On the other hand, stronger IFN response in female macrophages is conserved all the way to birds 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1 F, G) compared to C57BL/6J background [ 9 ], as only C57BL/6J mice exhibited increased oxidative stress [ 35 ]. In addition, C57BL/6J displayed insulin resistance and alterations in their metabolic response to diet-induced obesity compared to C57BL/6N mice, further highlighting the importance of the genetic background when assessing metabolism [ [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%